2018
DOI: 10.1159/000489914
|View full text |Cite
|
Sign up to set email alerts
|

Add-On Effect of Angiotensin Receptor Blockade (Candesartan) on Clinical Remission in Active IgA Nephropathy Patients Treated with Steroid Pulse Therapy and Tonsillectomy: a Randomized, Parallel-Group Comparison Trial

Abstract: Background/Aims: Angiotensin receptor blockers (ARBs) may be beneficial for clinical remission during conventional therapy with tonsillectomy and steroid pulse (TSP) for active IgA nephropathy. Methods: Seventy-seven patients with active IgA nephropathy were randomly assigned to the control arm with conventional regimen (TSP followed by oral prednisolone) (n = 37) or the ARB arm with conventional regimen plus ARB candesartan for the first 6 months (n = 40). Patients not achieving proteinuria remission at 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Overall, 635 patients were enrolled in 10 RCTs, including 327 in the treatment group and 308 in the control group/placebo, and the follow-up period ranged from 1 to 276 months. 8 of these studies were from Asia (9–11, 13, 14, 1618), 2 from Europe (12, 15), and 5 studies included children and minors (age < 18 years) (9, 12, 15, 16, 18). After further analysis of the RCTs, we found that 2 studies were ACEI+ARB compared with control group/placebo (9, 13), 5 studies were ACEI compared with control group/placebo (1012, 15, 17), and 4 studies were ARB compared with control group/placebo (10, 14, 16, 18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 635 patients were enrolled in 10 RCTs, including 327 in the treatment group and 308 in the control group/placebo, and the follow-up period ranged from 1 to 276 months. 8 of these studies were from Asia (9–11, 13, 14, 1618), 2 from Europe (12, 15), and 5 studies included children and minors (age < 18 years) (9, 12, 15, 16, 18). After further analysis of the RCTs, we found that 2 studies were ACEI+ARB compared with control group/placebo (9, 13), 5 studies were ACEI compared with control group/placebo (1012, 15, 17), and 4 studies were ARB compared with control group/placebo (10, 14, 16, 18).…”
Section: Resultsmentioning
confidence: 99%
“…4). In terms of the effect of RASI on proteinuria levels in IgAN patients, 2 RCTs (60 patients) were ACEI+ARB compared with control group/placebo (9, 13), and 4 studies (353 patients) were ACEI compared with control group/placebo (1012, 15, 17), 4 studies (274 patients) were ARB compared with control group/placebo (10, 14, 16, 18). We used a random effects model analysis and the results suggested that alone use of ACEI (MD=–0.75, 95%CI: –1.28–0.21, P =0.006) or ARB (MD=–0.56, 95%CI: –0.82–0.30, P < 0.001) or a combination of ACEI and ARB (MD=–0.63, 95%CI: –0.87–0.38, P <0.001) significantly reduced the levels of proteinuria in patients with IgAN (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, we did not find an association between renal arteriolar remodeling and eGFR decline in patients with IgA nephropathy. As many patients with IgA nephropathy receive combination treatment with tonsillectomy and steroid pulse therapy, as part of a very common approach in Japan [34] and given that most of these patients achieve remission of proteinuria, as we have shown in an interventional study [35], defining the impact of renal arteriolar remodeling in IgA nephropathy might be difficult. However, renal RAS might be associated with subsequent renal progression as UAGT tended to be associated with the eGFR decline independent of basal renal arteriolar WLR in patients with IgA nephropathy, similar to that recently shown in patients with CKD [26].…”
Section: Discussionmentioning
confidence: 98%
“…Depressive patients usually suffer from emotional loss, loss of interest and pleasure, and lack of concentration or fatigue [15]. Candesartan is a new type of oral angiotensin receptor blockers (ARBs) used in clinic because it selectively blocks the combination of Ang II and AT1R, thus blocking the biological effect of Ang II [16]. Some studies have shown that candesartan can reduce the loss of peripheral cells, thus delaying the development of diabetic retinopathy [17][18][19].…”
Section: Discussionmentioning
confidence: 99%